Design, simulation and manufacturing of a connecting rod from ultra-fine grained material and isothermal forging. (January 2016) - Fuertes, J.P.; Luis, C.J.; Luri, R.; Salcedo, D.; León, J.; Puertas, I.
Abstract: In this research work, a study on the mechanical properties of isothermal forging for connecting rods is made from previously ECAP (Equal Channel Angular Pressing)-processed AA1050 and AA5083 aluminium alloys. This severe plastic deformation (SPD) process is used in order to achieve a starting material with a submicrometric structure, thus improving the mechanical properties of the part. In this study, the design and the experimentation process is shown, where this involves the design stage by finite element simulations, the experimental tests and the use of metallographic techniques for the required properties to be analysed. It is observed that there is an improvement in the mechanical properties when the starting material is ECAP-processed before carrying out the isothermal forging. This improvement consists in an increase of 20% in the hardness of the final connecting rod which also possesses a microstructure grain size of 500 nm. To come to these conclusions, the results obtained with the connecting rods manufactured by isothermal forging from previously ECAP-processed material are compared with those conventionally manufactured. Therefore, the feasibility and the advantages of the industrial manufacturing of mechanical components by isothermal forging from ECAP-processed material are demonstrated here as mechanical properties are achieved, as well as a better flow of the material and at a lower forging temperature. In the existing bibliography, there are no research works dealing with the manufacturing of connecting rods from ultra-fine grained material and that is the reason why this present study is considered to be of scientific and technological interest, and therefore, it may be considered to be at the frontline of current knowledge.